Theoretical problems of fight against corruption (Journal of actual problems of jurisprudence, 2018)
Corruption, to a regret, is that social evil which is inherent practically in all states of the world independently from the political and state system. Proceeding from its danger, destructive and negative social and economic and legal consequences, the states try to undertake various measures, in that number of legislative character, for eradication and the prevention of corruption. In this article authors consider concept of corruption, thought and definition of some scientists about the corruption phenomena, parts of the international legal documents accepted for fight against corruption, the main categories corruption the phenomenonKey words: strategy for fight against corruption, convention, corruption, official, public debt, personal benefit.